Strategi Adaptasi Organisasi dalam Menghadapi Tantangan Pandemi Covid-19 terhadap Praktik Sumber Daya Manusia: Analisis dari Konteks Global - Rahmawati; Tukiran, Martinus (IJOSMAS, 2024)
This article discusses organizational adaptation strategies in facing the challenges of the COVID-19 pandemic on human resource practices. Against the backdrop of ongoing digital transformation in the workplace, this research aims to identify the strategies needed by organizations and human resource managers to overcome the impact of the COVID-19 pandemic. The research method used is a systematic literature review approach, involving identification, evaluation and synthesis of existing research studies. The results of the discussion show that the COVID-19 pandemic has encouraged organizations to adopt virtual human resource development strategies, reskilling and upskilling, as well as anticipating digital transformation in the workplace. In conclusion, strategic adaptation, attention to employee welfare, and accelerated technology adoption are the keys to facing the challenges the COVID-19 pandemic poses to human resource practices.